Influence of Lightweight Foamed Concrete as Backfill Material on Stress and Deformation of Buttressed Earth-Retaining Wall. (8th September 2021) - Qiu, Youqiang; Liu, Yang; Zhang, Liujun; Wang, Zhanqi
Abstract : Controlling settlement and earth pressure behind retaining wall in soft soil area are ongoing practical problems for the construction and operation of highway, which are mainly caused by the poor nature of soft soil. To reduce the pushing force on retaining wall and subgrade settlement, the authors propose the use of lightweight foamed concrete as subgrade filler behind the buttressed earth-retaining wall. However, the mechanical properties and deformation behavior of the buttressed earth-retaining wall remain unknown when lightweight foamed concrete is used as a backfill behind the wall. To solve this problem, a scale model of the subgrade filled with lightweight foamed concrete behind the buttressed earth-retaining wall is established to determine its stress and deformation characteristics under different factors. Lateral earth pressures and wall displacements at different elevations of the retaining wall model were monitored during the tests. Then, a series of orthogonal experiments are conducted to analyse and compare the effects of overload, density, and replacement thickness of lightweight foamed concrete on the earth pressure and displacement of this retaining wall. The results show that the size of earth pressures at the same position of retaining wall is affected by overload, density, and replacement thickness of lightweight foamed concrete, but its change of distribution form is only related to the replacement thickness of this backfill. Additionally, the primary-secondary relations of different factors' influence extent on the forces and deformation of the buttressed earth-retaining wall filled with lightweight foamed concrete as backfill are obtained by using range analysis method.